Influence of Private Forest Land to Farmers Welfare in Yogyakarta Special Province - Su Ritohardoyo (Forum Geografi, 1999)
Forest people land use pratices with economic and ecological orientation have been developed in the vicinity of forest areas. Nevertheless, policy makers view this development as detrimental to the forest it self. Forestry programs directed to accommodate public participation are uniformly designed and implemented, ignoring the physical and social variantion of rural areas. Thus there is a need for research on spatial variation of the social forestry program especially related to its success and impact on welfare. The research is carried out in Yogyakarta speial province employed a survei method and spatial approach. Stratified cluster sampling is used on the basis of variations in physiographic characteristics. Secondary data are also collected in forms of literatures and previous research in the field. Primary data are obtained through a structured interview using a set of questionnaires. Data are analyzed using simple tabulation method as well as statistical techniques.The research shows that in general people forest land use has been sucessfully implemented in the province. It is important to note that a more successfull implementation of people forest land use is found in the private rather than government initiated forest. In the less accessible areas people forest land use activities are much more successfull than in the accessible ones. Social forestry land use in the volcanic slope physiography is much better than that in either undulating or karst areas. Among important factors affecting the success of people forest land use are land ownership, education level, technology, land accessibility and percentage of plant growth. It is also confirmed that accessibility is the most important factor affecting the success of an people forest land use. The research also reveals that people forest land use has been very important in improving the farmers welfare. A composite indicator shows that the welfare of farmers is much improved after the adoption of people forest land use, with the highest achievement is obtained by farmers in the volcanic slopes.